Aerosolized Thyroid Hormone Prevents Radiation Induced Lung Fibrosis - Li, Long; Nie, Xiaoqi; Yi, Minxiao; Qin, Wan; Li, Fang; Wu, Bili; Yuan, Xianglin (Frontiers in Oncology, 2020)
Radiation induced lung fibrosis (RILF) is a common late complication after radiotherapy without effective treatment. Thyroid hormone (TH) is known to reverse bleomycin-induced pulmonary fibrosis in recent study. We therefore sought to examine TH effect in RILF. Aerosolized TH delivery prevented pulmonary fibrosis according to either micro-computed tomography scans or histological evaluations, without significant changes in serum THs in a murine model of RILF by attenuating TGF-β1 and phosphorylated Smad2/3 expressions and reducing the accumulation of M2-like macrophages. Furthermore, hypothyroidism was significantly correlated with RILF in a retrospectively analyzed data from nasopharyngeal carcinoma patients treated by intensity-modulated radiation therapy with a median follow-up time of 25.5 months. Together, aerosolized TH may prevent RILF by inhibiting the TGF-β1/SMADs signaling pathway.